Beyond assessments: Exploring strategies for Afro-Descendant students’ success in Costa Rica - Dianala M. Bernard (Goodwood Publishing, 2023)
Purpose: This research aims to critically analyze the potential ramifications of comprehensive assessments on marginalized communities, with a specific focus on Afro-descendant students in the Caribbean/Atlantic region of Costa Rica. It intends to identify the potential effects of these assessments and propose policy and practice adjustments that can enhance their educational outcomes. Research methodology: This research analyzes the recent assessment requirements and the historical background of educational assessments in Costa Rica and explores alternative teaching methods, including culturally responsive pedagogy (CRP) and the impact of the dialect and language continuum. Furthermore, the potential benefits of integrating the International Baccalaureate (IB) philosophy into the curriculum of all public schools are also investigated. Results: Based on the analysis conducted, recommendations for policy and practice changes to address the potential impact of assessments on Afro-descendant students include creating a culturally responsive curriculum, recognizing non-standard dialects, using alternative assessment approaches, and emphasizing consideration of marginalized communities' needs and experiences in educational policy and practice decisions. Limitations: This review does not provide an empirical investigation but rather synthesizes existing literature and provides recommendations for future research. Contribution: This research significantly contributes to the existing literature on educational policy and practice in marginalized communities, particularly in relation to students of African descent in Costa Rica and suggests ways to improve their educational outcomes. Its insight can be of interest to policymakers, educators, and future researchers in education and social justice.